Abdomen agudo perforativo y aplicación del proceso de atención de enfermería - Ruilova Ullauri, Adriana Elizabeth; Murillo Zambrano, Denisse Jacqueline (Machala : Universidad Técnica de Machala, 2019)
The acute abdomen is responsible for 10% of the visits to the emergency department, with 50% admitted; of which 30% to 40% are surgically operated; and from 5% to 10% of these interventions are by perforation of viscera and relating with generalized peritonitis, can lead to septic shock, constitute a high degree of morbidity and mortality. Its causes vary between obstruction, diverticulitis, neoplasms, and ulcers. It is characterized by abdominal pain type colic, rigid abdomen (in table), absence of elimination of gases, vomiting, diarrhea, diaforesis, hyperthermia, dehydration, tachycardia, bradycardia and arterial hypertension, leukocytosis. It is diagnosed by anamnesis, complete blood count and image examinations, of immediate surgical treatment. Its complications vary: sepsis and septic shock, where the prognosis will depend on immunologic and physiological factors of the patient. The objective of the present study is to identify the causes of the emergence of the acute perforative abdomen and its complications in patients of 61 years male sex and application of the nursing care process according to the theory of Marjory Gordon. The clinical case is a 61-year-old male patient, with a pathological history of arterial hypertension and type 2 diabetes mellitus. He goes to the Theophilus Dávila Hospital, in the city of Machala on the 19-07-2018. For presenting abdominal pain of 2 weeks of evolution , is self-medicated while staying ambulatory and at 14 days the abdominal table is exacerbated presenting pain type colic of great intensity, abdomen distended (in table), absence of elimination of Flatos, with the valuation. Vital Signs: TA: 132/79 mmhg, T°: 38.7 ° C, FR: 31 rpm, FC: 99 ppm, SO2:94%. Physical examination: Presents pale facies, Algic, diaphoretic, rigid abdomen, globulous, painful to superficial and deep palpation; also, emphasizing glucose: 279 mg/dl. According to evaluation of surgery, with diagnosis of acute inflammatory abdomen, the exploratory laparotomy is performed emergent with surgical findings: Fecal peritonitis 1800 cc, colon right and transverse, with ischemic and necrotic signs, perforation of 2 cm at level of transverse colon, tumor mass in a straight-sigmoid junction of more or less 10 cm, adhered to bladder wall and infiltrating abdominal wall; Performing a total colectomy plus ileostomy. It passes to recovery room in poor clinical conditions with diagnosis of septic shock, where it is valued by UCI, and it is indicated reference to health unit of greater complexity. At 2 days, it is transferred, in the same clinical conditions with diagnosis of sepsis not specified. The method applied is the analysis of the clinical history and scientific articles of relevant information. With the exhaustive analysis of the case, it is determined that the perforation was due to the obstruction in rectosigmoid by stenosis at the level of tumor mass, that prevented the outflow of fecal feces and gases, causing the intestinal loops to cause ischemia and necrosis of right and transverse colon and for 2 weeks evolution time. Therefore, it’s concluded that the cause was intestinal obstruction and the complication, is septic shock and that in addition the colonic perforations do not occur frequently.
El abdomen agudo es el responsable del 10% de las visitas al servicio de urgencias, siendo el 50% ingresados; de los cuales del 30 al 40% son intervenidos quirúrgicamente; y del 5 al 10% de estas intervenciones son por perforación de vísceras y relacionándolo con la peritonitis generalizada, puede llegar a producir hockeys séptico, constituyen un alto grado de morbimortalidad. Sus causas varían entre obstrucción, diverticulitis, neoplasias, úlceras. Se caracteriza por presentar: dolor abdominal tipo cólico, abdomen rígido (en tabla), ausencia de eliminación de gases, vómitos, diarrea, diaforesis, hipertermia, deshidratación, taquicardia, bradicardia e hipertensión arterial, leucocitosis, se diagnostica mediante anamnesis, hemograma completo y exámenes de imagen, de tratamiento quirúrgico es inmediato, sus complicaciones varían: sepsis y shock séptico; el pronóstico dependerá de factores inmunológicos y fisiológicos del paciente. El objetivo del presente estudio es identificar las causas de la aparición del abdomen agudo perforativo y sus complicaciones en paciente de 61 años sexo masculino y aplicación del proceso de atención de enfermería según la teoría de Margory Gordon. El caso clínico es de un paciente de sexo masculino de 61 años con antecedentes patológicos de hipertensión arterial y diabetes mellitus tipo 2, acude al Hospital Teófilo Dávila de la ciudad de Machala el día 19-07-2018 por presentar dolor abdominal de 2 semanas de evolución, se automedica permaneciendo ambulatorio a los 14 días se exacerba el cuadro abdominal presentando dolor tipo cólico de gran intensidad, abdomen distendido (en tabla), ausencia de eliminación de flatos, a la valoración; signos vitales: TA: 132/79 mmhg, T°: 38.7°C, FR: 31 rpm, FC: 99 ppm, SO2: 94%; al examen físico: presenta facies pálidas, álgicas, diaforético, abdomen rígido, globuloso, doloroso a la palpación superficial y profunda; destacando también la glucosa: 279 mg/dl. Según valoración de cirugía con diagnóstico de abdomen agudo inflamatorio, realiza laparotomía exploratoria emergente con hallazgos quirúrgicos: peritonitis fecal 1800 cc, colon derecho y transverso con signos isquémicos y necróticos, perforación de 2 cm a nivel de colon transverso, masa tumoral en unión recto-sigmoidea de más o menos 10 cm, adherido a pared de vejiga y pared abdominal infiltrante; realizando una colectomía total más ileostomía. Pasa a sala de recuperación en malas condiciones clínicas con diagnóstico de shock séptico, es valorado por UCI, indica referencia a unidad de salud de mayor complejidad, a los 2 días es transferido, en iguales condiciones clínicas con diagnóstico de septicemia no especificada. El método que se aplica es el análisis de la historia clínica y de artículos científicos de información relevante. Con el análisis exhaustivo del caso se determina que la perforación fue debido a la obstrucción en rectosigmoide por estenosis a nivel de masa tumoral que impidió la salida de heces fecales y gases, haciendo que las asas intestinales se dilaten causando isquemia y necrosis de colon derecho y transverso y por tiempo de evolución de 2 semanas. Por lo tanto, se concluye que la causa fue la obstrucción intestinal y la complicación es el shock séptico y que además las perforaciones de colon no se presentan frecuentemente.
Keywords: ABDOMEN AGUDO PERFORATIVO; SEPSIS ABDOMINAL; SHOCK; ATENCION DE ENFERMERIA